Pengaruh Model Make A Match Berbantuan Media Permainan Ular Tangga Terhadap Keaktifan Siswa Pada Pembelajaran IPAS Kelas III SDN 87 Singkawang - Ari Purnomo Aji; Haris Rosdianto; Erdi Guna Utama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: 1) determine the effect of the Make A Match Learning Model assisted by the Snakes and Ladders Game Media on Learning Activity in Grade III IPAS Learning SDN 87 Singkawang; 2) find out how much influence the Make A Match Learning Model can increase Learning Activity in Grade III IPAS Learning SDN 87 Singkawang; 3) find out the student's response in using the Make A Match Learning Model assisted by the Snakes and Ladders Game Media on Learning Activity in Grade III IPAS Learning SDN 87 Singkawang. The research method is Pre-Experimental Design with One-Group-Pretest-Posttest-Design. Data collection techniques in this study used non-test techniques, namely, observation and questionnaire. The instruments in this study are, namely, Student Activity Observation Sheets and Response Questionnaire Sheets. The population in the study were all third grade students of SDN 87 Singkawang. The research sample was taken by non probability sampling with a saturated sample totaling 22 third grade students. The prerequisite test carried out is the normality test using SPSS 25 for windows software. The first hypothesis testing uses the N-gain test, the second hypothesis is the Dependent t-test and the third uses the average formula. The results showed that: 1) There is an increase in student learning activeness by using the Make A Match model assisted by snakes and ladders game media with the N-Gain test of 0.68 classified in the medium category; 2) Based on the results of calculating student data using the SPPS application using the Dependent T-Test Test, it is known that the Sig. (2-tailed) is 0.000 <0.05, then H0 is rejected and Ha is accepted. So that the results obtained are, there is an effect of using make a match learning assisted by snakes and ladders media on student learning activeness; 3) based on the average data of the response questionnaire that researchers gave to students after the Post Test, the percentage of each indicator of student response was in the very good and sufficient category. The highest percentage is in the conclusion indicator which is 100%. From each of these indicators that can affect students' responses in learning. Then the average percentage of the overall student response was obtained at 93% in the very good category. So the results obtained are, there is a positive student response to the Make A Match model assisted by snakes and ladders media.